Emerging trends in the developments of low power design technique - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2020)
In this paper is introduced a low power design technique for developing more reliable, functional, and more cost-effective handheld cellular telephones, portable computers, and peripherals. The portability requirements of handheld computers and other portable devices have placed tremendous pressure on electronic equipment designers, who need to deal with restrictions in the size of electronic units and power consumption. Even though battery technology is continuously improving, including reduced power consumption of processors and displays, extensive and continuous use of network services aggravates these issues. Now the onus is on the research and industrial communities to extend battery life and reduce weight. Equally, research on new techniques and technologies continues, to carefully manage energy consumption in mobile devices, while still providing continuous and fast connections to services and applications. This paper also discusses the novel trends in the developments and advancements in the area of low power Very Large Scale Integration (VLSI) design, dynamic power dissipation static power loss in Complementary Metal Oxide Semiconductor (CMOS), and advanced low power technique. Though low power as a well-established domain that undergone lots of developments from transistor sizing, process shrinkage, voltage scaling, clock gating, etc., to adiabatic logic are elaborated.Â Â